Sn(salen)-derived SnS nanoparticles embedded in N-doped carbon for high performance lithium-ion battery anodes. Issue 58 (17th June 2020) - Jin, Aihua; Kang, Narae; Um, Ji Hyun; Ko, In-Hwan; Kim, Min-Seob; Kim, Kookhan; Kim, So Hee; Yu, Seung-Ho; Sung, Yung-Eun
Abstract : SnS nanoparticles embedded in N-doped carbon are prepared by using Sn(salen) and exhibited outstanding electrochemical performance for lithium-ion batteries. Abstract : By simple pyrolysis of a tin salen complex [Sn(salen)] and sulfur powder at 700 °C, SnS nanoparticles with ∼20 nm thickness homogeneously embedded in nitrogen-doped carbon are prepared. When applied as lithium-ion battery anodes, the SnS/N–C nanocomposites exhibited long cycling stability and excellent rate capability.